2008
DOI: 10.1038/jcbfm.2008.154
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Angiotensin II Attenuates VEGF-Mediated Blood—Retinal Barrier Breakdown in Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) is the leading cause of vision loss as a major complication of diabetes mellitus. The blood-retinal barrier (BRB) breakdown is a critical early event in the pathogenesis of DR. It has been known that the rennin-angiotensin system (RAS) is important in the progression of the DR via angiotensin II (Ang II), the effector of RAS. In this study, we showed that blockade of Ang II attenuates vascular endothelial growth factor (VEGF)-mediated BRB breakdown in DR. In streptozotocin-induced dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 35 publications
4
60
0
3
Order By: Relevance
“…9,10 Accordingly, systemically administered ACE1 inhibitors and AGTR1 antagonists attenuate retinal microvascular disease in diabetic rodents by decreasing vascular hyperpermeability, acellular capillaries, and the expression of angiogenic factors, such as vascular endothelial growth factor. 9,11 Despite the clear success of systemic RAS blockade in diabetic rodents, systemic suppression in humans has led to only marginal improvement. AGTR1 blockade decreased the incidence of DR in individuals with type 1 diabetes and improved mild and moderate DR in those with type 2 diabetes.…”
mentioning
confidence: 99%
“…9,10 Accordingly, systemically administered ACE1 inhibitors and AGTR1 antagonists attenuate retinal microvascular disease in diabetic rodents by decreasing vascular hyperpermeability, acellular capillaries, and the expression of angiogenic factors, such as vascular endothelial growth factor. 9,11 Despite the clear success of systemic RAS blockade in diabetic rodents, systemic suppression in humans has led to only marginal improvement. AGTR1 blockade decreased the incidence of DR in individuals with type 1 diabetes and improved mild and moderate DR in those with type 2 diabetes.…”
mentioning
confidence: 99%
“…Most of these pathogenic actions are inhibited or attenuated by pharmacological blockade of the RAS either at the levels of ACE or the AT receptors and are associated with the downregulation of VEGF and VEGF receptor-2 [41]. Kim et al [45] showed that perindopril (an ACE inhibitor) attenuated VEGFmediated BRB breakdown in rats with streptozotocininduced diabetes mellitus (STZ-DM). It is also noteworthy that candesartan (an AT-R blocker) inhibited retinal accumulation of the AGE product pentosidine in spontaneously diabetic Torii rats [46].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…(3) [41][42][43][44][45][46][47][48][49]. Angiotensin II (AT) binds and activates two primary receptors, AT1-R and AT2-R.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…VEGF may also be expressed in, to a lesser extent, endothelial cells, astrocytes, RPE, and RGCs. However, Müller cells are the major source of VEGF in DR (Arjamaa and Nikinmaa, 2006;Kim et al, 2009b). VEGF plays a leading role in inducing retinal inflammation and vascular leakage that occurs as a consequence of diabetes.…”
Section: P0615mentioning
confidence: 99%